Comparative Experimental Investigation of Environmentally Non-Hazardous Rapeseed Oils Using Technical Reliability Indicators - Kučera Marián; Drmla Jakub; Aleš Zdeněk (Acta Technologica Agriculturae)
The procedures of tribological diagnostics use oil filling as a resource for multidimensional and complex information about the phenomena, changes, and modes of wear in systems. The purpose was to investigate the possibilities of evaluating two physicochemical parameters [kinematic viscosity at 40 °C (KV40) and total acid number (TAN)] of 6 natural non-edible oils according to chemical composition by means of two methods in laboratory conditions using a tribometer. Evaluation was based on the hypothesis that the oil is considered relatively good if its changes in selected diagnostic properties remain within permissible limits for at least 1000 operating hours. One of the procedures is the assessment of bio-based hydraulic oils on a reciprocal comparison of properties. The following method is based on the monitoring of suitably chosen diagnostic signals that will indirectly rate the technical condition of the oil filling according to changes in the dependent quantities. Results demonstrated that it is possible to assume the degradation of essential oil parameters to the limit condition, to use these data to determine the technical life of the oil filling, and to obtain the trends of relative operating time. In this way, it is possible to give users information about the quality of the oil used in specific operation conditions.